Body Mass Index and the measurement of obesity - David Madden (University College Dublin, UCD School of Economics, 2006)
This paper proposes a new method of measuring obesity using Body Mass Index (BMI) data. Conventional measures which simply count the number of individuals with BMI in excess of an upper limit ignore the extent by which individuals exceed BMI limits and also the increased risk ratios for various conditions associated very high levels of BMI. This paper suggests that measures currently used in the poverty literature can be usefully applied to measure obesity and provide us with measures which may be more relevant from a policy perspective. The approach is applied to data for Ireland.
hdl:10197/782
Keywords: I12; I31; I32; 330; Obesity; Body Mass Index